Synthesis and optimization selective ion-imprinted polymer for the elimination of Ca II ions using Taguchi design - AL-Maibd, Rafah; Al-Ashaq, Wissam; Zainuddin, Norhazlin; Ibrahim, Nor Azowa; Samsudin, Intan Nureslyna; Yahaya, Noorfatimah; Kamaruzaman, Sazlinda (Springer Netherlands, 2021)
One of the most important problems associated with calcium measurement is the possibility of underdiagnosed due to a false prediction of hypercalcemia results. Ion imprinting has become one of the fast growing technologies that have gained a lot of attention recently especially in the area of materials science. The present work proposes the synthesis and characterization of ion-imprinted polymer (IIP) in the form of porous film for the removal of Ca (II) from aqueous solution and human blood serum. Ca (II)-IIP films are prepared from mixing of two naturally formed biopolymers cellulose and sodium alginate, CaCl2, ECH, EDTA are used as the source of template ions, cross-linker and extraction agent, respectively. Taguchi method is used to optimize the synthesis and adsorption parameters of the new developed IIP. The optimum IIP films are characterized using FTIR, TGA, FESEM and XRD for determining the performance of the imprinting process achieved. PH dosage, initial concentration, reusability, selectivity, isotherm and kinetic study are investigated for the optimized IIP in Ca (II) aqueous solution. The resulted optimum conditions are pH 5.9, initial concentration (50 mg/l), dosage (300 mg) and 90 min contact time. It was clear from the adsorption data that the Ca (II) sorption by Ca (II)-IIP was fitted with the Langmuir isotherm model. The Langmuir adsorption constants for the adsorption of Ca (II) at room temperature are calculated to be (0.017 L/mg) and the R is 0.9469. The rate of removal of Ca (II) by Ca (II)-IIP is sustained between 98.99 and 86.12% for five periods. Furthermore, findings show that the Ca (II)-IIP is can successfully applied for the removal of free Ca (II) ions in human blood serum.